2001
DOI: 10.1016/s0022-5347(05)66085-5
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Cancer Detection in Veterans With a History of Agent Orange Exposure

Abstract: Agent Orange may have a role in the causation of some types of cancer but we identified no significant relationship of prostate cancer with Agent Orange exposure in patients referred for prostate biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 14 publications
3
24
1
1
Order By: Relevance
“…Zafar and Terris evaluated patients who were referred for prostate biopsy. 8 Of 400 patients who were referred for biopsy in that study, 32 patients reported exposure to Agent Orange. Although Zafar and Terris observed a slightly increased rate of prostate cancer in the group with Agent Orange exposure (41% vs 34%), the increase was not statistically significant.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Zafar and Terris evaluated patients who were referred for prostate biopsy. 8 Of 400 patients who were referred for biopsy in that study, 32 patients reported exposure to Agent Orange. Although Zafar and Terris observed a slightly increased rate of prostate cancer in the group with Agent Orange exposure (41% vs 34%), the increase was not statistically significant.…”
Section: Discussionmentioning
confidence: 97%
“…Although there is sufficient evidence linking soft tissue sarcomas, Hodgkin disease, and non-Hodgkin lymphoma with Agent Orange exposure, 4 evidence of the risk of subsequent prostate cancer has been much less robust. [5][6][7][8][9][10] Operation Ranch Hands, a longitudinal study that was conducted on Air Force veterans, identified no increased incidence of prostate cancer compared with a similar cohort of veterans. However, that study did observe an increased risk compared with the standard US population of white men.…”
mentioning
confidence: 99%
“…A prevalence study was conducted among 400 Vietnam veterans referred for prostate biopsy (Zafar and Terris, 2001). Thirty-two veterans who reported Agent Orange exposure were compared to a sample of 96 unexposed veterans.…”
Section: Review Of Epidemiologic Studiesmentioning
confidence: 99%
“…Early studies failed to show a significant association between AOe and PCa detection 12,13 ; however, the majority of studies including larger more recent studies have shown a positive association with PCa 1013 . The small sample size in the studies finding positive but not statistically significant associations warrants caution as Type II error could account for these non-significant findings since these studies were not powered to find an association with the strength we observed in our study.…”
Section: Discussionmentioning
confidence: 95%
“…The effect of AOe on the risk of PCa detection has been an area of some scientific debate. Early studies failed to demonstrate a significant association between AOe and PCa detection 12,13 ; however, the majority of studies, including larger, more recent studies, have demonstrated a positive association between AOe and PCa. [10][11][12][13] The small sample sizes in the studies that reported positive but statistically nonsignificant associations warrant caution, because a type II error may account for these nonsignificant findings, in that those studies were not powered to identify an association with the strength we observed in our current study.…”
Section: Discussionmentioning
confidence: 98%